Os movimentos reivindicatórios dos policiais militares e os impasses das lutas por direitos em Mato Grosso - Almeida, Franklin Epiphanio Gomes de (2018)
The study deals with the impasses present in the mobilizations that occurred within the Military Police of the State of Mato Grosso due to the restriction of access to certain rights, especially with regard to the rights to unionization and strike. By having these rights denied by the current legislation, the possibilities of collective struggle and the demand for rights of the military police officers become scarce and ineffective, damaging even more their living and working conditions. Military legislation criminalizes military police officers movements by allowing their manifestations and mobilizations to be characterized as military crimes of mutiny or revolt. The research problem consists in investigating how and under what conditions the demands of the military police officers of the State of Mato Grosso occurred between 1988 and 2017. This is an exploratory study of descriptive nature with a qualitative approach, carried out through consultations of documentary sources and semi-structured interviews with leaders of military police officers associations, family members of military police officers, former general commanders and militants of the protest movements during the study period. The study showed that because of the prohibition of unionization and strike, the military police officers began to support the organization of their wives and relatives in the creation of spaces of fight to defend their claims, later transformed the various police associations - recreation and leisure spaces - in political spaces, that is, spaces of debate and mediation of their claims to the various instances of state power. However, given the limits of the struggle for rights in the capitalist system and the hierarchical, authoritarian and centralizing nature of the police institution in Brazil, such strategies have not been sufficient to produce significant changes in their living conditions, allowing only specific achievements, whether in relation to their working conditions, salary and career, or in relation to their political organization, discipline and hierarchy. It also showed that the manifestations within the Mato Grosso Military Police are not rare occurrences and that the most radical movements were generally carried out by the wives and relatives of the police officers as a result of the impossibility of direct punishment of these militants.